2022
DOI: 10.3389/fimmu.2022.938011
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies during infectious diseases: Lessons from malaria applied to COVID-19 and other infections

Abstract: Autoimmunity is a common phenomenon reported in many globally relevant infections, including malaria and COVID-19. These and other highly inflammatory diseases have been associated with the presence of autoantibodies. The role that these autoantibodies play during infection has been an emerging topic of interest. The vast numbers of studies reporting a range of autoantibodies targeting cellular antigens, such as dsDNA and lipids, but also immune molecules, such as cytokines, during malaria, COVID-19 and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Autoimmune activity contributing to prothrombotic and inflammatory processes in the context of systemic infections has become increasingly appreciated (30,65). Here, we evaluated whether prothrombotic autoimmune processes play a role in the pathogenesis of pediatric malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune activity contributing to prothrombotic and inflammatory processes in the context of systemic infections has become increasingly appreciated (30,65). Here, we evaluated whether prothrombotic autoimmune processes play a role in the pathogenesis of pediatric malaria.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence of autoantibody generation during malaria and other infectious diseases, while their potential pathological role remains insufficiently known [11]. Autoimmune hemolytic anemia, antiphospholipid antibodies, new fluorescence type of ANA, and different ANCA patterns had previously been described in patients suffering from malaria [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been observed that antibodies produced during an infection can trigger neuropsychiatric complications due to a cross-reaction in which antibodies recognize pathogen antigens but may also recognize self-antigens[ 68 , 69 ]. It has been proposed that genetic factors of the host and infectious agent influence the development of these complications[ 70 ].…”
Section: Other Immunological Mechanisms Inducing Psychiatric Complica...mentioning
confidence: 99%